(untitled) (Alberta Journal of Educational Research, 2007)
This article discusses methodological and philosophical issues linked to action research. The concepts of subjectivity and objectivity—potential sources of bias that mislead researchers in dealing with these concepts—and how to cope with them are discussed. Controversial issues of truth in positivism, postpositivism, and other schools of philosophy are considered. Finally, the article touches on validity criteria, validity types, and how to grapple with validity in action research.